2020
DOI: 10.1088/1755-1315/469/1/012012
|View full text |Cite
|
Sign up to set email alerts
|

CBR Laboratory Analysis for Determining The Number of Compaction Tracks to Achieve Field CBR

Abstract: Compaction is the process of grounding the soil by removing air from the pores of the soil mechanically (beaten, crushed and so on) Compaction is carried out with the aim of improving the technical properties of the soil, namely obtaining the densest soil conditions (maximum solid state). In the process of compaction water content also plays a significant role to achieve maximum density value. Water is a lubricant for the soil to help unify the aggregate and remove air in the compaction process. From the resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Lakshami et al (2019) related the resilient modulus with CBR values of different subgrade soils such as clayey sand (SC), silty sand (SM), and well-graded sand (SW). Recently, Srihandayani et al (2020) related the bearing capacity of the soil with CBR values. Rezende and Carvalho (2003) studied the application of quarry wastes as a base layer under the flexible pavements.…”
Section: Introductionmentioning
confidence: 99%
“…Lakshami et al (2019) related the resilient modulus with CBR values of different subgrade soils such as clayey sand (SC), silty sand (SM), and well-graded sand (SW). Recently, Srihandayani et al (2020) related the bearing capacity of the soil with CBR values. Rezende and Carvalho (2003) studied the application of quarry wastes as a base layer under the flexible pavements.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the lower hydraulic conductivity associated with an additional compaction energy level could make them suitable for use as compacted soil in geotechnical work [11]. Srihandayani et al (2020) [12] describe how to project laboratory compaction results in the field (a Vibro-roller grinding machine) based on finding the number of compaction trajectories. Lindh (2004) [13], concluded that compaction of stabilized soil is necessary to ensure high quality and the required service life of the stabilized material, citing different studies by researchers.…”
Section: Introductionmentioning
confidence: 99%